Integrasi Teknologi Informasi dalam Pembelajaran Seni sebagai Strategi Pembelajaran Abad ke-21 di SD - Jaka Nugraha; Eris Risnawati; Reza Maulana; Ika Dwi Lestari (Universitas Bumigora, 2026)
The rapid development of information technology has encouraged changes in art learning in elementary schools to become more creative, interactive, and aligned with 21st-century skills. However, its implementation still faces several challenges, including limited teachers’ digital competence, unequal availabilityof digital facilities, and low utilization of technology in art learning. This study aims to analyze the integrationof information technology in art learning as a 21st-century learning strategy in elementary schools. The studyemployed aq ualitative approach with a descriptive design through observation, interviews, and documentation.Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealedthat the use of digital media, design applications, learning videos, and interactive platforms was able toimprove students’ creativity, collaboration, communication, and engagement in learning activities. Otherfindingsindicatedthatteachers’digitalcompetenceandlimiteddigitalfacilitiesremainedthemainobstaclesinImplementing technology-based art learning. Theoretically,this study strengthens the concept of constructivistand technology-based learning in supporting the holistic developmentof 21st-century skills among elementaryschool students.